The Image of Refugees and the Features of its Development in Lithuanian Online Newspapers - Matas, Darius (Žurnalistikos tyrimai, 2017)
The considerable number of refugees fleeing to Europe has an impact on countries’ economic, political and social agenda, as well as the processes of society. The European refugee (migrant) crisis, which began in 2015, brought out not only different attitudes toward refugees among European Union politicians, but also revealed how diverse the coverage of national media may get on the refugee topic. Refugees flee to Europe from various countries and diverse cultural backgrounds. However, society lacks the knowledge about their religious beliefs, lifestyles and outlooks. Moreover, the media has the power to decide which events and individuals to portray, and in such a way constructs the audience’s perception about the world they live in. Refugee-related messages in the media usually occur in a negative context: terrorist attacks, refugee deaths, criminal activity and protests. However, the media does not only construct, but also has the power to change prejudice toward refugees, ensuring that one of its aims is interaction between diverse social groups. The author combines quantitative and qualitative research methods for media messages and analyzes dominant stereotypes about refugees in Lithuanian online media. The types of refugee-related publications are also examined. Three research periods were chosen: 1-31 July 2015, 1-30 November 2015 and 1-31 January 2016. The main goals are to theoretically discuss the media’s role and peculiarities in shaping certain images which society maintains, as well as to define the stereotypes and their role in society. Lithuanian online newspapers are commercial institutions, which – in order to compete in the market – strive to engage consumers. Delivering messages quickly and in large quantities often matters more than their content and the reliability of sources. This, in turn, leads to the information being distorted or superficial. Lithuanian newspapers construct a negative refugee image, where the most dominant images of refugees are as individuals who are uncontrollable, aggressive and prone to commit crime, being either gang members, terrorists or benefit recipients.